Pengaruh Penambahan Hidroksiapatit dari Cangkang Telur Ayam Terhadap Kekerasan Permukaan GIC - Mawadara, Putri Ajri; Mozartha, Martha; K, Trisnawaty (Jurnal Material Kedokteran Gigi, 2016)
Hydroxyapatite (HA) is a bioceramic with excellentbiocompatible properties, and composition and crystal structure similar to apatite in the human dental structure and skeletal system. A number of researchers have attempted to evaluate the effect of the addition of HA powders to increasemechanical properties of restorative dental materials. In this study, HA was synthesized using chicken eggshell as calcium source for synthesizing HA by using precipitation technique. The aim of this study was to determine the effect of incorporation of eggshell-derived HA on the surface  hardness GIC (Fuji IX GP). Specimens were divided into two groups: group GIC without incorporation of HA as control group (n = 16) and group GIC with incorporation of 5% HA as experimental group (n = 16). Total of specimens were 32 cylinders 5mm diameter and 2mm height. Surface hardness GIC was measured with vickers microhardness tester. Data wasanalyzed by unpaired T-test. The mean of surface hardness for GIC control group was 51.37 ± 1,63VHN and the experimental group was 56.60 ± 1,22HVN. The results T-test showed a significant difference between groups (p<0.05). It can be concluded thatincorporation of eggshell-derivedHA could increasesurface hardness of GIC.